Patterns of same-day alcohol and cannabis use in adolescents and young adults with risky alcohol use. (4th March 2022) - Coughlin, Lara N.; Bonar, Erin E.; Bohnert, Amy S. B.; Blow, Frederic C.; Bauermeister, José A.; Cross, Yazmyn; Cunningham, Rebecca; Young, Sean D.; Walton, Maureen A.
Abstract: Same-day alcohol and cannabis use is relatively common in adolescents and young adults, constituting a higher-risk behavior relative to single-substance use. However, the association between quantity of alcohol and cannabis use on co-use days is understudied. We examined the association between the quantity of alcohol and same-day cannabis use with a multilevel regression analysis in a sample of youth (16–24 years old) with risky alcohol use. Participants reported one or more days of alcohol and cannabis over the past month ( N  = 468). Quantity of cannabis use was highest on heavy drinking days [ M  = 0.91 grams, SD  = 0.68] followed by moderate drinking days ( M  = 0.78 grams, SD  = 0.63), and lowest on days without alcohol use ( M  = 0.74 grams, SD  = 0.64, p  < 0.001). In multilevel modeling analyses, adjusted for clustering within individuals, greater quantity of drinking on a given day was associated with greater cannabis use (estimate = 0.03, p  < 0.001). When using alcohol and cannabis on the same day, greater alcohol use was associated with greater cannabis use. Preventing days of heavy use of multiple substances, particularly among at-risk drinkers, may complement interventions addressing co-use generally to prevent substance-related consequences.